Implementasi Pendapatan, Belanja dan Pelaporan Keuangan Desa - Siti Atikah; Sapto Hendri; Intan Rakhmawati (Jurnal Riset Akuntansi, 2019)
This study aims to describe the various efforts of the village government in obtaining income and spending it, in accordance with applicable regulations. This study will examine types of village income and expenditure that are in accordance with the characteristics of the region and village customs, which are referred to as local wisdom. The ability of human resources is suspected to be an obstacle to implementing all stages of financial management. This study examines the contents of available documents, namely “Laporan Pertanggungjawaban Pendapatan dan Belanja Desa” and “Laporan Kekayaan Milik Desa”. The results show that LSR and GRI villages have the ability to obtain income from “Badan Usaha Milik Desa (BUMDES)” activities, parking fees, and third-party assistance. In terms of village expenditure management, GRI, LSR, LO, and BPB are able to demonstrate activities that originate from the participation and local wisdom. In terms of openness in village financial management, LSR and BPB have activities that support the attractive and communicative village sites with their visitors. The constraints come from an insufficient understanding of financial managers on the village financial reporting process, although it had been helped by the application of the available village financial system.